Arabic Accounting Language and Understanding Gap Field study in the Iraqi environment - Hwaish Allawi Al-Shujairi, Mohammed (Journal of Research in Finance and Accounting, 2021)
The problem of the multiplicity and conflict of accounting terminology raises a major crisis in the Arabic accounting language. This crisis becomes even greater when the accounting concepts and their linguistic connotations are incompatible, while the crisis reaches its climax when accounting concepts are poorly represented by the economic phenomena they represent. As a result of this crisis, the emergence and growth of a gap of understanding among the beneficiaries, contributes to diminishing the usefulness of accounting information in the decisions of the beneficiaries, and contributes to affecting the status of the profession and accounting education in the Arab environment. In this context, the current research aimed to determine the dimensions of that problem and its implications for the Iraqi environment. The descriptive, analytical, quantitative approach based on the exploratory study was used by designing a special questionnaire form to survey the opinions of a sample of academics and professionals working in this environment. Several conclusions were reached, the most prominent of which is the reality of the problem of multiple accounting terms and the conflict of some accounting and semantic concepts in the Arabic accounting language. While a set of recommendations were presented, the most important of which is the need to study and standardize accounting terminology in the Arab accounting linguistic structure to enhance the utility and role of the Arabic accounting language.